From Graz to Ljubljana? Towards Discovery of the Origin of the Hren Choirbooks - Grabnar, Klemen (De musica disserenda, 2015)
There are five scribal hands evident in the Hren choirbooks. The main scribe for these choirbooks was Georg Kuglmann; the others are unknown. Three scribes (among them, Kuglmann) worked closely together and formed part of a scribal workshop at Graz. The presence of two other scribal hands suggests that not all the repertory was copied in Graz. The Missa L’homme armé of Palestrina was probably copied in Innsbruck in the late sixteenth century (given the paper type), and a few responses in falsobordone style were added in later years, perhaps in Ljubljana.